Severe 5, 10‐methylenetetrahydrofolate reductase deficiency: a rare, treatable cause of complicated hereditary spastic paraplegia. (30th January 2018) - Perna, A.; Masciullo, M.; Modoni, A.; Cellini, E.; Parrini, E.; Ricci, E.; Donati, A. M.; Silvestri, G.
Abstract : Background and purpose: Juvenile‐ or adult‐onset forms of severe 5, 10‐methylenetetrahydrofolate reductase (MTHFR) deficiency manifesting as complicated hereditary spastic paraplegia have rarely been described. Methods: Two siblings with mental retardation developed a progressive spastic paraparesis in their late teens. Their diagnostic assessment included extensive neurophysiologic, neuroimaging and metabolic studies. Results: Brain magnetic resonance imaging showed occipital white matter alterations, and electromyography documented a mixed polyneuropathy. Severe hyperhomocisteinemia (>150 μmol/L) associated with the characteristic amino acid profile suggested a diagnosis of severe MTHFR deficiency, confirmed by MTHFR direct sequencing. Treatment with betaine and vitamins benefitted patients' symptoms and diagnostic features. Conclusions: Severe MTHFR deficiency can be a rare, treatable cause of autosomal recessive complicated hereditary spastic paraplegia. Its screening should be part of the diagnostic flowchart for these disorders.